Variação sazonal de parâmetros ecofisiológicos em matrizes de umbuzeiro - Costa, Raimundo Nonato Moraes (2023)
The seasonally dry tropical forests suffer water deficit throughout the year and most of the existing species there are deciduous, being adapted to the recurrent bad weather caused by seasonality. Spondias tuberosa Arruda, the umbuzeiro, is a species adapted to the Brazilian semi-arid region, fruitful, perennial and endemic with great capacity to withstand conditions of low water availability. The objective of this work was to evaluate the physiological changes as a function of seasonality in adult plants of umbuzeiro, seeking to understand how the survival mechanisms of gas exchange, photosynthetic apparatus, leaf dynamics of carbohydrates react to seasonal changes. The study was carried out at Lagoa de Pedra Farm, located in the municipality of Cubati, Paraíba, Brazil, in a natural orchard of umbu trees. Data were collected in the study area in the months of April, May and December 2020 and January and April 2021, related to precipitation, temperature, leaf area index, soil moisture in twenty individuals, whose data analysis showed effects on fluorescence , gas exchange, leaf chlorophyll indices, water relations and leaf carbohydrate contents. Gas exchange was closely related to water availability, showing seasonal variations in stomatal conductance (GS), leaf photosynthetic rate (A), transpiration (E), intrinsic water use efficiency (EiUA) and instantaneous carboxylation efficiency (EiC). The correlation between instantaneous water use efficiency (EUA – W/E) and intercellular CO2 concentration (Ci) did not show significant differences from the dry to the rainy season. A similar event occurred in relation to the variables of maximum chlorophyll fluorescence (Fm), variable fluorescence/maximum fluorescence (Fv/Fm) and variable fluorescence/initial fluorescence (Fv/F0), that is, there was no significant difference. Chlorophyll levels (a) and (b) decreased significantly in the dry season compared to the rainy season, indicating the plant's difficulty in maintaining the integrity of its photosynthetic machinery in the face of water restriction. The concentrations of carbohydrates in the leaf, in the form of glucose, did not present significant differences in the evaluated periods. In relation to starch and sucrose, there was a significant increase in the dry season. During the evaluation period, there was a decrease in soil moisture in the dry season, accompanied by the relative moisture levels of the leaf, with no significant change in leaf temperature and deficit in leaf vapor pressure. The flux density of photosynthetic photons showed a significant decrease in the rainy season. Umbu plants have adaptive mechanisms to stressful conditions of hydric deficit imposed by seasonality, considering the small variations in the glucose content from the dry to the rainy season, and in the accumulation of starch and sucrose contents in the dry season for later mobilization. With low rates of stomatal conductance, the umbu tree reveals good intrinsic efficiency in water use. The chlorophyll b when subjected to hydrical stress is more affected than chlorophyll a in umbu plants.